1998
DOI: 10.1002/(sici)1520-6327(1998)38:1<19::aid-arch3>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Novel insecticidal peptides fromTegenaria agrestis spider venom may have a direct effect on the insect central nervous system

Abstract: Fractionation of venom from an agelenid spider, Tegenaria agrestis, resulted in the isolation of a family of three peptides with potent insecticidal activity. These peptide toxins, TaITX‐1, ‐2, and ‐3, whose sequences were revealed from cloned cDNAs, each consist of 50 amino acid residues, six of which are cysteines. They appear to be amidated at their C‐termini and exhibit greater than 90% sequence identity. Unlike other reported spider toxins, the TaI toxins are processed from precursors containing no propep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…However, this analysis indicates that 1T0Z (from the Asian scorpion Buthus martensi Karsch) and 1I25 (from the Chinese bird spider O. huwena) may have anti-coleopteran properties due to the fact that they are in the same branch as 1WWN and 1TI5, respectively ( Figure 1). Studies have shown that insecticidal toxins purified from arthropod venoms exert their effects via specific interactions with ion channels and receptors in the central or peripheral nervous system (De Lima et al, 2007;Bloomquist, 2003;Johnson et al, 1998;Fletcher et al, 1997). B. martensi Karsch venom has four peptides related to the excitatory insect toxin family and 10 related to the depressant insect toxin (Goudet et al, 2002).…”
Section: The Phylogenetic Relationship Of Insecticidal Toxins and Thesupporting
confidence: 62%
“…However, this analysis indicates that 1T0Z (from the Asian scorpion Buthus martensi Karsch) and 1I25 (from the Chinese bird spider O. huwena) may have anti-coleopteran properties due to the fact that they are in the same branch as 1WWN and 1TI5, respectively ( Figure 1). Studies have shown that insecticidal toxins purified from arthropod venoms exert their effects via specific interactions with ion channels and receptors in the central or peripheral nervous system (De Lima et al, 2007;Bloomquist, 2003;Johnson et al, 1998;Fletcher et al, 1997). B. martensi Karsch venom has four peptides related to the excitatory insect toxin family and 10 related to the depressant insect toxin (Goudet et al, 2002).…”
Section: The Phylogenetic Relationship Of Insecticidal Toxins and Thesupporting
confidence: 62%
“…4). A similar long delay is observed with the Tegenaria agrestis insect toxins TaI-TX-1 and TaITX-2, which are also thought to act within the central nervous system (Johnson et al 1998). However, ACTX is more active than these toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect is somewhat controversial, since neuronal barrier systems are traditionally thought to protect the CNS from protein toxins (Zlotkin et al 1988). Experiments on a novel toxin from the North American spider Tegeneria agrestis (Johnson et al 1998) showed that it was inactive on peripheral sensory and motor nerves of insects, but had a potent excitatory effect on the CNS. Another study (Fletcher et al 1997) showed that 1 lM x-atracotoxin-HV1 (ACTX) from the Australian funnel web spider Hadronyche versuta, partially blocked calcium currents in voltage-clamped cockroach neuronal somata.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of their capacity to paralyze and kill insects at low doses, they appear to target the nervous system of insects with high affinity. Some of these insecticidal peptides have been isolated from venom of the spider Tegenaria agrestis (TaITx1 -3) and their full sequences have been determined from cloned cDNA [94]. These toxins consist of 50 amino acid residues, 6 of which are cysteines.…”
Section: Insecticidal Spptxs Without a Defined Mode Of Actionmentioning
confidence: 99%